Integrating social justice concerns into economic evaluation for healthcare and public health: A systematic review. (February 2018) - Dukhanin, Vadim; Searle, Alexandra; Zwerling, Alice; Dowdy, David W.; Taylor, Holly A.; Merritt, Maria W.
Abstract: Social justice is the moral imperative to avoid and remediate unfair distributions of societal disadvantage. In priority setting in healthcare and public health, social justice reaches beyond fairness in the distribution of health outcomes and economic impacts to encompass fairness in the distribution of policy impacts upon other dimensions of well-being. There is an emerging awareness of the need for economic evaluation to integrate all such concerns. We performed a systematic review (1) to describe methodological solutions suitable for integrating social justice concerns into economic evaluation, and (2) to describe the challenges that those solutions face. To be included, publications must have captured fairness considerations that (a) involve cross-dimensional subjective personal life experience and (b) can be manifested at the level of subpopulations. We identified relevant publications using an electronic search in EMBASE, PubMed, EconLit, PsycInfo, Philosopher's Index, and Scopus, including publications available in English in the past 20 years. Two reviewers independently appraised candidate publications, extracted data, and synthesized findings in narrative form. Out of 2388 publications reviewed, 26 were included. Solutions sought either to incorporate relevant fairness considerations directly into economic evaluation or to report them alongside cost-effectiveness measures. The majority of reviewed solutions, if adapted to integrate social justice concerns, would require their explicit quantification. Four broad challenges related to the implementation of these solutions were identified: clarifying the normative basis; measuring and determining the relative importance of criteria representing that basis; combining the criteria; and evaluating trade-offs. All included solutions must grapple with an inherent tension: they must either face the normative and operational challenges of quantifying social justice concerns or accede to offering incomplete policy guidance. Interdisciplinary research and broader collaborations are crucial to address these challenges and to support due attention to social justice in priority setting. Highlights: Priority setting in healthcare impacts the distribution of societal disadvantages. We review methods suitable for integrating social justice into economic evaluation. Suitable methodological solutions face normative and operational challenges.